Measuring Service Quality and User Satisfaction of Universitas Terbuka’s Ruang Baca Virtual (RBV) Using SERVQUAL and EUCS - Denisha Trihapningsari; Dwi Astuti Aprijani; Mayang Anglingsari Putri; Fonda Leviany (LPPM Universitas Bhinneka Nusantara, 2026)
This study aims to measure the service quality and user satisfaction of the Ruang Baca Virtual (RBV) application within Universitas Terbuka’s (UT) digital library and to identify priority dimensions requiring improvement. A quantitative survey approach was employed using two structured questionnaires based on the SERVQUAL and End User Computing Satisfaction (EUCS) models. SERVQUAL was applied to assess five dimensions of service quality (tangibles, reliability, responsiveness, assurance, and empathy), while EUCS evaluated five dimensions of user satisfaction (content, accuracy, format, ease of use, and timeliness). The SERVQUAL gap analysis was conducted using a percentage comparison approach against the ideal score to determine priority improvement areas. The research included 100 participants, where 50 respondents evaluated service quality using the SERVQUAL method, and the remaining 50 respondents measured user satisfaction using the EUCS approach. The results indicate that all SERVQUAL and EUCS dimensions fall within the “satisfied” category. Empathy and reliability emerged as key strengths in service quality, while ease of use and accuracy were identified as main strengths in user satisfaction. However, responsiveness and assurance (SERVQUAL), as well as format and timeliness (EUCS), exhibited relatively larger gaps, indicating areas requiring improvement. These findings provide a comprehensive descriptive evaluation of RBV performance and offer strategic insights for enhancing digital library services in distance learning environments.